2020
DOI: 10.22541/au.159248834.46935661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dexamethasone vs. betamethasone for preterm birth: a systematic review and network meta-analysis

Abstract: Objective To compare the effectiveness and safety of dexamethasone versus betamethasone for preterm birth (registered in PROSPERO CRD42017078006). Search strategy We searched in MEDLINE, EMBASE, Cochrane Library, LILACS, Clinical Trials.gov, International Clinical Trials Registry Platform, reference lists and contacted field experts. Selection criteria, data collection and analysis Randomized controlled trials comparing any corticosteroids against each other or against placebo. Three researchers independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Importantly, a recent randomized double-blind controlled trial including 1509 fetuses who received antenatal corticosteroids, showed no significant difference in neurosensory disability at 2 years of age between those treated with dexamethasone and those treated with betamethasone [ 54 ]. Consistent with this, a recent meta-analysis of 45 trials including 11,227 women and 11,878 infants, found no difference between dexamethasone and betamethasone on neonatal death, neurodevelopmental disability, IVH and birthweight [ 55 ]. In contrast to the consistent short-term benefits seen in clinical trials, preclinical studies from a wide range of animal models have raised concerns that antenatal steroids may have adverse effects on neurological outcomes.…”
Section: Treatments Currently In Clinical Use For Preterm Infantsmentioning
confidence: 67%
“…Importantly, a recent randomized double-blind controlled trial including 1509 fetuses who received antenatal corticosteroids, showed no significant difference in neurosensory disability at 2 years of age between those treated with dexamethasone and those treated with betamethasone [ 54 ]. Consistent with this, a recent meta-analysis of 45 trials including 11,227 women and 11,878 infants, found no difference between dexamethasone and betamethasone on neonatal death, neurodevelopmental disability, IVH and birthweight [ 55 ]. In contrast to the consistent short-term benefits seen in clinical trials, preclinical studies from a wide range of animal models have raised concerns that antenatal steroids may have adverse effects on neurological outcomes.…”
Section: Treatments Currently In Clinical Use For Preterm Infantsmentioning
confidence: 67%
“…However, it can decrease the development of chorioamnionitis and fetal death. 32 These findings could be attributed to the pharmacokinetic properties of each formulation. A 1:1 mixture of betamethasone phosphate and betamethasone acetate has a fast and sustained release in which its plasma levels could be detected after 14 days of a single intramuscular injection.…”
Section: Discussionmentioning
confidence: 99%
“…Auch die letzte Metaanalyse zu diesem Thema, in die die Daten aus 45 Studien von 11 227 Frauen und 11 878 Kindern einflossen, konnte keine Unterschiede hinsichtlich der perinatalen und maternalen Morbidität zwischen Dexamethason und Betamethason nachweisen. Die Inzidenz der Sectio caesarea wurde in dieser Metaanalyse nicht näher untersucht 15 .…”
Section: Wahl Des Kortikosteroidsunclassified
“…The most recent meta-analysis on this topic, which included data from 45 studies covering 11 227 women and 11 878 children, found no differences with regard to perinatal and maternal morbidity rates between dexamethasone and betamethasone. The meta-analysis did not investigate the incidence of cesarean section 15 .…”
Section: The Choice Of Corticosteroidmentioning
confidence: 99%